Building consensus on transition of transplant patients from paediatric to adult healthcare. Issue 8 (1st June 2010) - Webb, Nicholas; Harden, Paul; Lewis, Clive; Tizzard, Sarah; Walsh, Grainne; Wray, Jo; Watson, Alan
Abstract : Objective: Despite improvements in recent years at many centres, there remains an overall lack of consistency in the healthcare and support services provided to young people during their transition from paediatric to adult transplant units. Concerns that such deficiencies may be causally related to subsequent graft loss through patient non-concordance have prompted calls for the delivery of a more patient-centred service. To address these issues, representatives from major transplantation centres in the UK (cardiac, hepatic, renal) and across all disciplines were brought together to produce a series of consensus statements specifying key actions needed to improve the quality and consistency of transition healthcare. Design: Participants at the meeting included transplant physicians and surgeons from both adult and paediatric centres, allied health professionals (nurse specialists, psychologists, psychosocial support workers, transplant coordinators, youth workers), as well as young or adolescent transplant patients, their parents/carers and representatives of various support groups concerned with the young transitioning patient. The meeting consisted of presentations, group discussions (plenary and breakout) and a final discussion led by the seven participants who comprised the consensus panel. Results: Seven consensus statements emerged from the meeting, which are strongly representative of the current opinion of families and the UK transplant community. Conclusions: The actions they specify may therefore be seen as recommendations for timely and wide adoption, and as guidelines for best practice.